Totally laparoscopic treatment of intestinal tuberculosis complicated with bowel perforation: The first case report in worldwide literature with a brief review - Di Buono, Giuseppe; Vella, Roberta; Amato, Giuseppe; Romano, Giorgio; Rodolico, Vito; Saverino, Marta; De Lisi, Giovanni; Romano, Giorgio; Buscemi, Salvatore; Agrusa, Antonino (Frontiers in Surgery, 2022)
Introduction Bowel perforation is a relatively rare presentation of abdominal tuberculosis, whose diagnosis is challenging but fundamental in order to minimize morbidity and mortality. Laparoscopy is considered an effective modality for diagnosis but its role in surgical treatment is still not established. We reported the first worldwide case of totally laparoscopic treatment of intestinal tuberculosis complicated with bowel perforation. Case presentation A 30-year-old man with a history of weight loss, preceded by two years of non producting cough, was admitted to the Infectious Disease Department with a presumed diagnosis of tuberculosis. Microbiological culture test confirmed the diagnosis and patient undertook quadruple anti-tuberculous therapy. During hospitalization he presented sudden abdominal pain, fever and vomit. Abdominal CT scan showed small bowel perforation with granulomatous reaction. Laparoscopy was performed and revealed a 2 cm perforation on the medium ileum. Small bowel resection and totally intracorporeal side-to-side anastomosis was performed. No complication occurred until clinical follow up of two months. Conclusion In consideration of the increasing incidence of intestinal TB in both underdeveloped and Western countries, the diagnosis of this pathology should be taken into account in high risk patients. Probably, the diagnostic challenges and the emergency setting of intestinal TB with perforation and peritonitis, together with the lack of stardardized guidelines regarding the surgical management, make the use of laparoscopy apparently arduous, but the known advantages of laparoscopy and its technical feasibility should make it a conceivable option for the treatment of complicated cases.